Facilitators and barriers of fruit and vegetable consumption among Ugandans living with diabetes: a qualitative study - Aliza Hannah Stark; Norah Babirye; Tonny Kiyimba (BMJ Nutrition, Prevention & Health)
Background and aims In sub-Saharan Africa, a nutrition transition is driving increased consumption of ultraprocessed foods and reduced intake of vegetables and fruits. This shift contributes to high rates of diet-related non-communicable diseases like diabetes. This study aimed to identify the facilitators and barriers to consuming indigenous fruits and vegetables (IFVs) among individuals with type 2 diabetes (T2D) in Uganda.Methods Individuals living with T2D were recruited for focus group discussions (FGDs) based on a modified theoretical framework comprising three established theories. Purposive sampling targeted participants at a community diabetic clinic, recruited through village health workers. FGDs were audio-recorded, transcribed verbatim and analysed using inductive thematic content analysis. Recruitment continued until data saturation.Results Five FGDs (n=33) were conducted. Along with conventional pharmacotherapies, several indigenous vegetables and fruits were perceived as useful in maintaining normal blood glucose levels. Determinants for IFV use were identified at three ecological levels: personal, interpersonal and environmental. Major barriers included undesirable sensory attributes of IFV, lack of food processing and preservation skills, cultural and social influences, proximity to food markets, seasonality of IFV, financial constraints, unhygienic and harmful farm practices, media influence and limited accessibility to IFV. Major facilitators included fear-inspired dietary shift, attributed health benefits of IFV, presence of home gardens, literacy and budgeting skills, social and healthcare support, and skills in IFV preparation and preservation.Conclusion Despite acknowledging the importance of IFVs, barriers limit their consumption. Interventions should address personal obstacles, boost self-efficacy and change the food environment to promote healthy diets among Ugandan individuals living with diabetes.